GURU LAKI-LAKI PADA PENDIDIKAN ANAK USIA DINI - Widayati, Widayati (JPUD - Jurnal Pendidikan Usia Dini, 2016)
This research was determinate to describe about male teacher in early childhood education. This research was do in the TK Bahrul Maghfiroh Malang. This research is qualitative research with case study methode. Data analysis used Miles and Hubberman. Research data from observation, interview and documentasion. The result of this research show up about:1)The impact of male teachers for early childhood education, 2) Bahrul Maghfiroh institutions give consideration role of male teachers, 3) The process of learning the role of male teachers, 4)Public perceptions of male teachers. The role of male teachers have an impact on children's dress, emotional resilience, children's early understanding ofgender roles, the formation ofplay groups and play groups election. Bahrul Maghfiroh foundation as a boarding school is a major consideration institute son his role in male teachers. Curriculum implemented in kindergartens Bahrul Maghfiroh refers curriculum education office. learners are dominated by men. Learning methods are used storytelling, assignment method, field trips and debriefing. Utilizing instructional media used items available in schools. Approach to the children of male teachers need a figure of female teachers. Public perception of the role of male teachers who teach in kindergarten is still negative.